2019
DOI: 10.1021/acsami.9b03944
|View full text |Cite
|
Sign up to set email alerts
|

Poly(dimethylsilylene)diacetylene-Guided ZIF-Based Heterostructures for Full Ku-Band Electromagnetic Wave Absorption

Abstract: Zeolitic imidazolate frameworks (ZIFs), a group of metal-organic frameworks (MOFs), hold promise as building blocks in electromagnetic (EM) wave absorption/shielding materials and devices. In this contribution, we proposed a facile strategy to synthesize three dimensional ZIF-67-based hierarchical heterostructures through coordinated reacting a preceramic component, poly(dimethylsilylene)diacetylenes (PDSDA) with ZIF-67, following by carbonizing the PDSDA wrapped ZIF at high temperature. The introduction of PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(39 citation statements)
references
References 69 publications
0
39
0
Order By: Relevance
“…Furthermore, research on a coating system using conductive particles has been carried out; it is revealed that changes in conductivity tend to occur according to the binder and curing properties. In order to maximize shielding performance, it is important to maximize the conductivity of the conductive composite [23]. In addition, in general, the proportion of conductive particles increases, but the flexibility decreases.…”
mentioning
confidence: 99%
“…Furthermore, research on a coating system using conductive particles has been carried out; it is revealed that changes in conductivity tend to occur according to the binder and curing properties. In order to maximize shielding performance, it is important to maximize the conductivity of the conductive composite [23]. In addition, in general, the proportion of conductive particles increases, but the flexibility decreases.…”
mentioning
confidence: 99%
“…For the carbon species in the nanocomplex, the Raman spectra in Figs 2h and 3h show two typical peaks at 1350 cm −1 (D band) and 1580 cm −1 (G band). As well known, D band is related to defect/disordered carbons and G band represents stretching vibration of sp 2 graphitic carbons, where the integral intensity ratio (I D /I G ) can be applied to evaluate the graphitization degree of carbons [20]. The I D /I G for solid Fe/Co/C-800, solid Fe/ Co/C-900, hollow Fe/Co/C-800 and hollow Fe/Co/C-900 (the number denotes pyrolytic temperature) were 1.24, 1.06, 1.42 and 1.15, respectively.…”
Section: Pbas and Derived Fe/co/c And Fe/mn/c Nanocomplexes With Controllable Topologymentioning
confidence: 99%
“…As expected, the derived Co/C composite with well-dispersed magnetic cobalt nanoparticles inherited the topological structure of ZIF-67 crystals, showing effective absorption even at high temperature, i.e., a minimum reflection loss (RL min ) of −35.3 dB and an effective absorption bandwidth (EAB) of 5.8 GHz measured at 500°C [15]. The modified ZIF-67-derived hybrids with SiC [16], ZIF-8 [17,18], MXene [19], poly(dimethylsilylene)diacetylene (PDSDA) [20], carbon nanotubes (CNTs) [21], multiwalled CNTs (MWCNTs) [22,23], V 2 O 3 [24], Co 9 S 8 [25], etc., were extensively studied. Meanwhile, other MOFs including two-dimensional (2D) Co-MOF [26], Co-MOF-74 [27], MIL-88A(Fe) [28], MIL-101(Fe) [29], CPT-1-Co [30], and Fe III -MOF-5 [31] with controllable topologies also received attentions in the fields of EM functional materials.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] They mainly focus on ferrites, 6 low-dimensional carbon materials, 7,8 transition metals and their compounds, 9 and two-dimensional transition-metal carbides and nitrides (MXene). 10,11 At the same time, some novel light materials such as graphene or MXene aerogels have also been used to satisfy the requirements of EM wave-absorbing materials because of their high specific area and ultralow density. [12][13][14] However, at high temperatures, several problems such as oxidation of carbon materials transition from ferromagnetic to paramagnetic nature of magnetic materials above the Curie temperature have severely restricted their applications.…”
Section: Introductionmentioning
confidence: 99%
“…Electromagnetic (EM) wave‐absorbing materials with highly efficient and broadband absorption, light weight, and thin thickness are widely used to prevent EM pollution in various fields 1‐5 . They mainly focus on ferrites, 6 low‐dimensional carbon materials, 7,8 transition metals and their compounds, 9 and two‐dimensional transition‐metal carbides and nitrides (MXene) 10,11 . At the same time, some novel light materials such as graphene or MXene aerogels have also been used to satisfy the requirements of EM wave‐absorbing materials because of their high specific area and ultralow density 12‐14 .…”
Section: Introductionmentioning
confidence: 99%